Body weight changes and longitudinal associations with cognitive decline among community‐dwelling older adults. Issue 1 (20th February 2021) - Eymundsdottir, Hrafnhildur; Ramel, Alfons; Geirsdottir, Olof G.; Skuladottir, Sigrun S.; Gudmundsson, Larus S.; Jonsson, Palmi V.; Gudnason, Vilmundur; Launer, Lenore; Jonsdottir, Maria K.; Chang, Milan
Abstract: Introduction: We aim to investigate the longitudinal associations between changes in body weight (BW) and declines in cognitive function and risk of mild cognitive impairment (MCI)/dementia among cognitively normal individuals 65 years or older. Methods: Data from the Age Gene/Environment Susceptibility‐Reykjavik Study (AGES‐Reykjavik Study) including 2620 participants, were examined using multiple logistic regression models. Cognitive function included speed of processing (SP), executive function (EF), and memory function (MF). Changes in BW were classified as; weight loss (WL), weight gain (WG), and stable weight (SW). Results: Mean follow‐up time was 5.2 years and 61.3% were stable weight. Participants who experienced WL (13.4%) were significantly more likely to have declines in MF and SP compared to the SW group. Weight changes were not associated with EF. WL was associated with a higher risk of MCI, while WG (25.3%) was associated with a higher dementia risk, when compared to SW. Discussion: Significant BW changes in older adulthood may indicate impending changes in cognitive function.